Techno-Economic Assessment of Liquefied Petroleum Gas-Powered Alternative Electricity Critical Infrastructure Development in Nigeria’s South-West Geopolitical Zone - Ibikunle Ogundari; Olaleye SALU; Olajoke ILESANMI; Oladimeji BAKARE (Journal of Digital Food, Energy & Water Systems)
The decentralization of electricity authority in Nigeria has made it expedient for the South-West Geopolitcal Zone to develop strategic power generation infrastructure. This study assessed the techno-economic viability of the liquefied petroleum gas-powered alternative electricity infrastructure option in Southwestern Nigeria as a mitigation strategy to endemic inadequate grid power supply under the region's integrated electric power programmes. An energy project planning and foresight analysis methodology was used. The study showed that a 25 MW stand-alone LPG-based CHP power plant would require 8.567 acres of land, consume approximately 15.459 million kg of Liquefied Petroleum Gas (LPG) annually, while generating 210,240 MWh of electricity annually. This power plant initiative was considered to have acceptable risk (Payback Period = 9 years 3 months; Return on Investment = 10.73%) and viability at the minimum tariff of $0.11/kWh. It also had considerable annual CO2 emissions and fuel cost savings (255.75 metric kilotonnes and $137.58 million respectively) relative to diesel-based alternative power generation. The study recommended that the viability of the power plant be improved by reductions in operations costs. The study concluded that the LPG plant initiative was technically feasible, economically viable and environmentally friendly, and suitable for deployment in the study area.